Bilateral Oophorectomy and Heart Failure Risk: Mechanisms, Evidence, and Clinical Implications - Danya Z. Jafri; Sandesh Bhattarai; Mariah Hassan; Vibha Sharma; William H. Frishman; Wilbert S. Aronow (Cardiology in Review, 2026)
Abstract: Heart failure (HF), particularly heart failure with preserved ejection fraction (HFpEF), disproportionately affects women, yet female-specific and iatrogenic contributors to HF risk remain deeply underrecognized. Bilateral oophorectomy (BO) results in abrupt estrogen deprivation and has increasingly been associated with adverse cardiovascular outcomes, particularly when performed before natural menopause. This review examines the mechanistic and epidemiologic evidence linking BO to cardiovascular disease and HF, with particular attention to age at oophorectomy, estrogen deprivation, and the potential modifying role of estrogen replacement therapy (ERT). Growing evidence associates BO with increased cardiovascular morbidity, mortality, and HF risk, with the greatest risk observed among women undergoing premenopausal BO. Abrupt estrogen loss may contribute through endothelial dysfunction, increased vascular stiffness, adverse metabolic and inflammatory changes, neurohormonal activation, and myocardial remodeling—mechanisms that substantially overlap with HFpEF pathophysiology. ERT may mitigate some cardiovascular consequences of premature surgical menopause, although its effects appear dependent on age, timing of initiation, and route of administration. Recognition of BO as a female-specific cardiovascular risk factor may serve as a critical opportunity for earlier risk identification, targeted prevention, and individualized multidisciplinary care to reduce long-term cardiovascular and HF risk in women worldwide.